Effect of Biochar-Based Organic Fertilizer on the Growth of Maize in Cadmium-Contaminated Soil - Liyuan Mu; Hongyin Zhou; Ke Yang; Junlei Wang; Sijing Sun; Zhengli Lu; Lijuan Wang; Naiming Zhang; Li Bao (Agriculture)
China is vigorously promoting green, environmentally friendly, and sustainable agricultural practices, with a strong emphasis on the efficient recycling of biomass resources. In particular, in the field of fertilizer use, the country has clearly stated the need to reduce the application of chemical fertilizers, improve fertilizer use efficiency, and promote the substitution of chemical fertilizers with organic fertilizers. This study aims to explore the effects of different application rates of biochar-based organic fertilizers on soil-available nutrients, corn growth, and the inhibition of cadmium absorption and transfer in corn through field experiments. The experiment consisted of 10 treatments, including a blank control (CK), organic fertilizer at 1500 kg/ha (T1), 3000 kg/ha (T2), and 4500 kg/ha (T3), biochar-based organic fertilizer I at 1500 kg/ha (T4), 3000 kg/ha (T5), and 4500 kg/ha (T6), and biochar-based organic fertilizer II at 1500 kg/ha (T7), 3000 kg/ha (T8), and 4500 kg/ha (T9). The results indicate that the surface of the modified biochar exhibited significant fracturing and breakage, with an increase in pore size and pore number. Mn elements were successfully loaded onto the surface of the biochar, and the number of certain original functional groups was increased. Among all treatments, the T9 treatment (biochar-based organic fertilizer II at 4500 kg/ha) showed the best results in improving soil pH, organic matter, alkali-hydrolyzable nitrogen, and available potassium, significantly increasing these parameters by 0.69 units, 19.01%, 22.20%, and 36.24%, respectively, compared to the control. The T8 treatment (biochar-based organic fertilizer II at 3000 kg/ha) showed the best effect in reducing soil-available cadmium and cadmium content in corn grains, with reductions of 32.84% and 26.28%, respectively, compared to CK. The T9 treatment also had the most significant effect on increasing corn yield, plant height, crown width, and leaf length, with improvements of 64.08%, 0.16 m, 21.05%, and 9.28%, respectively, compared to CK. Correlation analysis revealed that corn yield, plant height, crown width, and leaf length were significantly positively correlated with soil pH, organic matter, alkali-hydrolyzable nitrogen, available phosphorus, and available potassium, while they were significantly negatively correlated with soil-available cadmium content. In summary, the application of organic fertilizers and biochar-based organic fertilizers I and II can improve soil pH, organic matter, alkali-hydrolyzable nitrogen, available phosphorus, and available potassium in cadmium-contaminated soils while also significantly enhancing corn yield and growth traits. Moreover, these fertilizers effectively reduce available cadmium in the soil and cadmium content in corn grains. Among the treatments, biochar-based organic fertilizer II performed the best in promoting crop growth, enhancing soil nutrient content, and reducing both soil-available cadmium and corn grain cadmium content, with the effectiveness ranking as follows: biochar-based organic fertilizer II > biochar-based organic fertilizer I > organic fertilizer. The results of this study provide a new approach to the resource utilization of agricultural waste and offer a theoretical basis for safe crop production in the context of heavy metal pollution.